Post-Covid Workplace Scenario - Employer and Employee Health and Safety - Palanisamy Sivaprakash; A.V.R. Akshaya (Occupational Health and Safety Society of Nepal, 2022)
The decreasing trend in the spread of the covid-19 infection has relaxed the restrictions imposed on the community, especially the working people. This working community, whether or not infected by the virus is now slowly turning back to work, along with the impacts of the lockdown. Though there is a decrease in the infection rate, there is always the possibility of infection at the workplace, as some percentage of the vaccinated people are also getting infected. It is absolutely necessary to follow the covid precautionary measures. Hence, it cannot be said that the normal situation has returned. The employer is in a state to manage a crowd comprising post-covid patients, caretakers of covid patients and non-affected groups. The literature works reporting on post covid scenario, precautionary measures to be taken and workplace, benefits of workplace social distancing and sanitation, and medical care needed for workers were reviewed. This paper discusses the post-pandemic workplace scenario, health and safety, sanitation among workers, awareness of precautionary measures and their behavioral changes.